Computationally Efficient Representation and Implementation of the Preisach-model of Hysteresis - Sari, Z. (Acta Technica Jaurinensis, 2013)
The paper deals with the details of representation and implementation of the Preisach-model of hysteresis in order to be efficiently applicable in numerical computations, particularly in finite element modelling and analysis.